Selection efficiency for growth performance of Menz sheep in a community-based breeding program - Abebe, A.; Banarjee, S.; Goshmie, S.; Bisrat, A.; Besufikad, S.; Zewdie, T.; Gizaw, Solomon (2020)
The study was undertaken to evaluate the efficiency of selection on growth performance of Menz sheep under a community-based breeding program (CBBP) from the period of 2009 – 2017. A total of 3996 lamb records (ram lambs 2025/ ewe lambs 1971) were used to evaluate the phenotypic and genetic factors affecting the growth traits of Menz sheep. REML in Wombat and General linear model on SAS (version 9.0) were used to evaluate selection efficiency for growth of Menz sheep. The least squares means and standard errors on phenotypic growth weight for birth, weaning age, six month age and yearling age were 2.58±0.004, 8.99±0.02, 13.28±0.02 and 19.94±0.06 kg, respectively. The effect of sex was significant (p<0.001) only for birth weight and no significance effect (p>0.05) was observed for weaning, six month and yearling weights. All growth traits were not affected by fixed effect of parity and birth type in this particular study. However, birth season and birth year had a great influence (p<0.0001) on all growth traits. The genetic trend on estimated breeding values (EBV) was not consistent across years and varied between sexes. The highest EBV for weaning, six month and yearling were recorded for the year 2013 and the lowest in 2009 (at weaning and six month) and 2015 (at yearling).The female EBV (at weaning, six month and yearling) was higher than male for the current (2017) and base population (2009).The responses to selection as compared to base population (2009) for birth, weaning, six month and yearling weight were – 0.00446Kg, + 0.11Kg, + 0.54Kg and + 0.75Kg respectively. This study indicates that improvement in body weight for Menz sheep through CBBP is possible; however, the response to selection varied across years and its pattern was irregular for the implemented years due to the problem on selection of breeding rams (lower availability of breeding rams) and management effect.